Design and analysis of microstrip antenna using negative index metamaterial approach - Alhawari, Adam Reda Hasan (2012)
Negative Index Metamaterials (NIMs) are extraordinary engineered materials. NIMs are the in-thing in the track of current research interest. It discovered a wide range of futuristic potential applications on super lenses, cloaking devices, filters and antennas. Hence, now it continuously sparks diverse areas of research to explore beyond previous discoveries, especially to produce more efficient microwave devices, specifically antennas. This study presents two different types of NIM structures. It is an attempt to improve the performance characteristics of two different classes of antenna designs. Parameters retrieval algorithm and full-wave simulation of prism-shaped structure were carried out to validate the negative index of refraction property of the proposed NIM structures. The results emphasize the prospect of the proposed NIM designs for being very promising alternatives to the conventional ones due to its broader spectrum of application and compatibility for various potential microwave devices, mainly when wideband or dual-band function is required. First, a three-unit cell NIM antenna is presented for ultra-wideband (UWB) applications. It was etched on FR4 epoxy substrate at an evident compact size of 25 x 25 x 1.6 mm3. This antenna exhibited a return loss of 94% bandwidth for voltage standing wave ratio (VSWR) less than 2 over the frequency band of 5.2–13.9 GHz, with a maximum gain and directivity of 3.85 dB and 5.45 dB, respectively, at 10.5 GHz. These measurement results show good agreement with those of simulations as well as good omni-directional characteristics within operating frequency band of the antenna. It does contribute compactness and high performance at low cost. Second, the conventional antipodal Vivaldi antennas (AVAs) suffer from some design problems like tilted beam; low or inconsistent directivity and gain; and larger size. A new compact AVA is introduced using linearly-tapered shape-loading structure due to crucial dependence on the space between the antenna arms, to further boost its performance especially when combined with NIM technology. Primarily, incorporation of NIM into this antenna design considerably overcomes the setbacks. A unique slitting approach harmoniously integrates the AVA with NIM where a single layer NIM piece is simply snug into the slit perpendicular to the middle antenna substrate. The final dimensions of the NIM antenna were 48 x 96 x 24 mm3. The NIM amplifies the capability to focus the entire beam to radiate onto the targeted direction. The measurement results are similar to simulations in terms of high gain, where the gain of the antenna was increased about 5 dB; directivity; and design flexibility within its operating frequency band (6.5–20 GHz). The contrast of overall performance between the new plain AVA and the NIM-improved ones evidently asserts the anticipated contribution of snug and boost method applied and significant potentials for a broad range of UWB applications, for instance, see-through-wall imaging and breast tumour detection.